Why is Self-Regulated Learning Strategy Important for Literal Reading? The importance of SRL for Literal Reading - Ratih Laily Nurjanah; Januarius Mujiyanto; Hendi Pratama; Dwi Anggani Linggar Bharati (Universitas Negeri Semarang, 2021)
Teaching reading involves consideration on implementing the appropriate strategies. University students, who are considered as adult readers, are expected to be able to learn independently supported by an appropriate strategy especially in reading classroom. Literal reading is mentioned as the lowest level of reading comprehension where it is considered effective to implement the Self-Regulated Learning strategy to lead them to be independent learners before dealing with higher level of comprehension. The objective of the study is to present the lecturers’ perception on why the SRL is important for Literal Reading students. This study is conducted with case study design where 2 lecturers of literal reading are interviewed to perceive their insight on how SRL is important for Literal Reading when it is implemented. The findings show that the SRL supports students of Literal Reading by helping them acquire the phases and learn how to self-regulate themselves by managing time, evaluating themselves, and reflecting the learning process. The limitations and recommendations are discussed.